A1.35 Syndecan-4 deficiency increases inflammation in experimental colitis. (24th February 2016) - Fröhling, M; Bettenworth, D; Paruzel, P; Echtermeyer, F; Lügering, A; Pap, T; Stratis, A
Abstract : Background and objectives: The ubiquitously expressed transmembrane heparan sulfate proteoglycan Syndecan-4 (Scd4) is able to act in different ways. By binding a variety of molecules, such as cytokines, it can function either as a decoy receptor or it can initiate signalling pathways. It has been also implicated in cell-matrix adhesion, cell migration, differentiation, proliferation and plays an important role during inflammation in rheumatoid arthritis. Our group showed that the loss of Sdc4 has a protective effect in cartilage damage, but in osteopontin-mediated liver damage, in which syndecan-deficiency increased the pathology. Because of these dual effects, we investigate the role of Sdc4 in murine experimental colitis. Material and methods: We performed DSS-induced colitis in Scd4 -/- and C57BL/6 WT mice at different time points. First, we analysed the Scd4 protein- and mRNA-level by immunofluorescence staining (IF) and quantitative real-time PCR, followed by measuring the course of colitis by weight loss, colon length, histological scoring of colonic modifications and IF of inflammatory marker cells. Colon-permeability was examined in vitro by using the Evans Blue method. Wound healing effects of Scd4 were analysed in vitro by performing scratch assay analyses withhuman epithelial colon cell line (T-84) and in vivo by colonoscopy of Scd4 -/- compared to WT mice. Results: The expression of Scd4 was downregulated in the course of colitis and was elevated during the recovery phase. DSS-treated Scd4 -/- mice lost dramatically more body weight compared to WT mice and the histological damage according to the Dieleman-Score was markedly elevated in the Scd4 -/- mice. Also, we found increased invasion of macrophages and granulocytes into the colon. In DSS-treated Scd4 -/- mice colon-permeability was higher compared to WT mice. The knockdown of Scd4 as well as treatment of T-84 cells with the anti-Scd4 antibody led to a delayed cell migration. Furthermore, colonoscopy experiments showed a decelerated wound healing effect in the Scd4 -/- mice. Conclusions: Our data indicate that Scd4 is a major molecule in the homeostasis of the colon epithelium. It exerts protective effects in intestinal inflammation with Scd4 deficiency leading to a higher permeability of the colon as well as a delayed cell migration and diminished wound healing.